The Carbon Stocks Estimation on The Green Belt of Mataram City - Aditya Riizki Kurniawan; Andi Chairil Ichsan; Markum (Jurnal Biologi Tropis, 2023)
Greenhouse Gases is a phenomenon where infrared radiation from sunlight is partly trapped in the atmosphere by greenhouse gases such as carbon dioxide (CO2), nitrogen oxide (N2O), and other gases, so that it can cause an increase in the temperature of the earth's surface. which results in climate change. This research aims to estimate carbon reserves in the Lingkar Selatan Green Belt of Mataram City. This research uses quantitative descriptive methods. The data collected is vegetation data. Vegetation data is collected by measuring the diameter and height of all vegetation or using the census method. Carbon stocks are estimated using allometric equations. The carbon reserves in the vegetation on the Lingkar Selatan Green Belt are 112.63 tons with 1432 individuals, with a stake level of 0.67 tons, a pole level of 13.75 tons, and a tree level of 98.13 tons. The highest amount of carbon reserves was found in the Canary (Canarium indicum) type at 33.91 ton and the lowest was in the matoa (Pometia pinnata) at 0.0012 ton.